DOI: 10.11606/t.23.2013.tde-28032014-160826
|View full text |Cite
|
Sign up to set email alerts
|

Espessura de tecidos moles nos diferentes tipos faciais: estudo em tomografias computadorizadas cone-beam

Abstract: AGRADECIMENTOSNinguém realiza qualquer objetivo pessoal sem companheirismo, ajuda ou exemplo.Por isso, gostaria de agradecer:À Juliana Noguti, minha companheira durante toda essa caminhada, e sua querida família.À minha avó Conceição, meus tios e tias, todos os primos e os que já nos deixaram. Aos colegas da Associação Brasileira de Ética e Odontologia Legal (ABOL) nas gestões de 2008-2010; 2010-2012, 2012-2014. Ter a oportunidade de conviver com pessoas extraordinárias nos dá dimensão de quanto mais temos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
19

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 47 publications
0
6
0
19
Order By: Relevance
“…After the survey conducted by Herrera, et al [3] came out, other contributions were made to forensic facial reconstruction, particularly tables of facial thicknesses of the soft tissue of Brazilians. In the same year of 2013, Beaini [8] added consistent results by supplying a new table with data on Brazilian adults, and proposed that standardized measurements of soft tissue thicknesses be performed using cone-beam computed tomography (CBCT) scans. This study examined the hypothesis that there would be differences in soft tissue thickness among individuals having different horizontal facial types, but no significant differences were found between facial types regarding the anatomical landmarks studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the survey conducted by Herrera, et al [3] came out, other contributions were made to forensic facial reconstruction, particularly tables of facial thicknesses of the soft tissue of Brazilians. In the same year of 2013, Beaini [8] added consistent results by supplying a new table with data on Brazilian adults, and proposed that standardized measurements of soft tissue thicknesses be performed using cone-beam computed tomography (CBCT) scans. This study examined the hypothesis that there would be differences in soft tissue thickness among individuals having different horizontal facial types, but no significant differences were found between facial types regarding the anatomical landmarks studied.…”
Section: Discussionmentioning
confidence: 99%
“…As for the methodology used, the measurement technique proposed by Beaini [8] had the advantage of using CBCT scans performed on live individuals in a sitting position. In this position, the effects of gravity on the facial tissues during image acquisition are not as strong as those on the tissues of corpses positioned in dorsal decubitus, or than those obtained by helicoidal computed tomography examinations on live patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Após o estabelecimento do perfil realizou-se a reconstrução facial manual e posteriormente a digital. Para a realização da determinação da espessura de tecidos moles, através de marcadores nos pontos craniométricos, foi utilizada a tabela desenvolvida por Beaini (2013). Concluiu-se que a reconstrução facial manual é possível de ser realizada por um operador leigo, sendo esta técnica a que mostrou maior subjetividade.…”
Section: ____________________________________________________________unclassified
“…After the establishment of the profile, manual and digital facial reconstruction were performed. For the determination of the thickness of soft tissues, through markers positioned in the craniometric points, it was used the table developed by Beaini (2013). It was concluded that manual facial reconstruction is possible to be performed by a lay operator, and this technique showed the highest subjectivity.…”
Section: Introductionmentioning
confidence: 99%